CHALLENGES AND OPPORTUNITIES OF USING PERSONALITY ASSESSMENTS IN THE ERA OF BIG DATA: A LITERATURE REVIEW - Mauliddiana, Arindra Pasca; Sarifah, Lailatus; Ramadhani, Kiki Katrin Trisya (PT Altin Riset Publishing, 2025)
The rapid advancement of digital technology has significantly influenced the field of personality assessment. This study explores the integration of big data into personality assessment practices and aims to identify both the challenges and opportunities that arise from this development. A systematic literature review was conducted, drawing from peer-reviewed journals, research reports, and recent case studies in the domains of psychology, data science, and human resource management. The findings reveal that big data allows for the continuous, real-time analysis of individual behavior patterns, enabling personality traits to be assessed in a more dynamic and contextual manner. This approach improves the precision and scalability of traditional assessment methods. However, several challenges persist, including concerns related to algorithmic bias, data privacy, informed consent, and ethical data governance. The study concludes that while big data has the potential to revolutionize personality assessment by making it more adaptive, predictive, and efficient, its implementation must be accompanied by robust ethical standards and regulatory frameworks. These safeguards are essential to ensure fairness, transparency, and accountability in the interpretation and use of personality data in both clinical and organizational settings.